Chow-Fraser et al. 2003 Frenchman's Bay - Chow-fraser P; Seilheimer T; McNair S; Eyles N (My University, 2025)
We conducted a two-year (2001-3) study to assess the impacts of urbanization on the water quality and fish habitat of Frenchman’s Bay, which is located in a highly urbanized watershed of Lake Ontario, Canada. During summer (end of May to mid-September) 2002, continuous monitoring devices were installed in two main tributaries, Amberlea Creek (below Hwy 401) and Pine Creek (above Hwy 401), and in two stations of the bay to measure a suite of physico-chemical parameters. Because of the low water levels, the monitoring was discontinued in the marsh, but was maintained in Amberlea and Pine Creeks from September 2002 to end of March 2003. We also carried out a parallel biweekly sampling program for nutrient and suspended solids at an open-water station during the summer of 2002 and one winter sampling trip in January 2003. Our investigation of the aquatic food-web included a survey of the aquatic plant community during the summer of 2001 and 2002, and a wetland-fish community survey that included nine sampling occasions between August 2001 and November 2002. The negative impact of runoff from Hwy 401 on the water quality of Amberlea Creek was clear: elevated levels of suspended solids and dissolved nutrients in summer, and elevated water turbidity and conductivity during winter could be linked directly to the onset of precipitation events. By comparison, water quality of the Pine Creek station, which is located well above the highway, did not exhibit the same degree of degradation, although we suspect that similarly degraded conditions would be found in Pine Creek downstream of Hwy 401. The heavier than normal rainstorms in July 2002 gave an excellent opportunity to observe the effects of storm events on creeks, while drier and hotter than normal weather in August allowed us a glimpse into how the marsh may behave if similar conditions anticipated by global climate change models are realized. We suggest that the marsh will become less hospitable to fish in such a scenario because water levels will be lower, water will stay warmer through the night, and become poorly oxygenated. Composite maps of physico-chemical conditions in Frenchman’s Bay, supplemented by information from a biweekly monitoring program revealed significant site-to-site differences in water quality. The three long-term sites we monitored during the summer of 2002 had very distinct characteristics. The Open station was deep (about 3.0 m), had warm surface water, lower conductivity, high DO content and low chlorophyll and turbidity. This description is consistent with the lower nutrient and suspended solids data reported for this station in a previous year. By comparison, the North station was shallow and warm, and seemed to be the most polluted of the three sites, with high conductivity, high chlorophyll and turbidity, and relatively low oxygen content. Like the North station, the South station was also shallow and warm, but was well- oxygented and had lower conductivity, chlorophyll and turbidity levels. There are a number of indicators of ecosystem health that can be used to assess the quality of fish habitat in a coastal wetland such as Frenchman’s Bay. In this study, we use a number of recently developed indicators based on physico-chemical and biological information (Chow- Fraser, unpub. data, McMaster University). A Wetland Water Quality Index (WQI) has been developed that is based on the findings from Crosbie and Chow-Fraser (1999) and Lougheed et al. (2001) in which water- and sediment-quality of wetlands located along all of the Canadian Great Lakes have been related to altered land uses in their watershed. In addition, we use information on macrophyte diversity as discussed in Lougheed et al. (2001), the Wetland Zooplankton Index (WZI) developed by Lougheed and Chow-Fraser (2002), and the periphyton index developed by McNair and Chow-Fraser (2003), and an unpublished index based on the biomass of zoobnethos to assess the ecological status of Frenchman’s Bay. All of the bioindicators point to Frenchman’s Bay as being moderately degraded, although in better condition than other urban coastal marshes along the Lake Ontario shoreline. That may explain why it still attracts a surprisingly large number of spawning and nursery fish throughout the spring and summer. Continuous water-quality monitoring should be continued for at least one more year in the creeks to supplement information in the current survey. We also recommend that the daily water samples taken in 2002 be processed and analyzed for nutrients and heavy metals (cadmium, copper, lead and zinc) to assess the degree and type of pollution from highway runoff. Water quality and the fish community in the marsh have already been well characterized in this study, although the fish community in the creeks will require further investigation. To improve habitat for the existing fish community, consideration should be given to enhancing and amalgamating the “islands” of emergent vegetation that currently exist in the north end of the lagoon. Since water quality in the north show obvious signs of pollution from the creeks, it would be desirable to redirect the highway runoff through a retention pond to remove the sediment and pollutants before the water is allowed to flow into the bay.
Keywords: Frenchman's Bay; Urbanization